'Postcolonial Islam' thought and rapped: Abd al Malik's Révolution Pacifique from within the French nation. (1st May 2015) - Spieser-Landes, David
Abd al Malik is a French rapper-writer born in 1975 of Congolese parents and raised throughout his childhood in a difficult neighbourhood of Strasbourg, France. While his family started out as Christian, his own spiritual journey took him through several stages of Islam: having, first of all, experienced first-hand the harsh reality of postcolonial France, i.e. living in the banlieue, he initially turned to religious extremism explicitly as a reaction to the postcolonial condition. Abd al Malik's thinking through of postcoloniality, however, is, in the end, far from simple, as he eventually integrated into his art and discourse the extremely opposed-to-extremism principles of Sufism and, as in fact, even some very traditional principles of the French Republic, making the association between 'Islam' and 'postcolonial' interestingly complicated indeed. This article scrutinizes in particular two of his books, Qu'Allah bénisse la France (2004) and Le Dernier Français (2012), and examines them under the lens of Jacques Rancière's 'politics of aesthetics' as a theoretical tool to better comprehend how Abd al Malik understands the link between Islam and the postcolonial as lying at the intersection of linguistics and politics.